The oligomerization regularities of individual unsaturated components of pyrolysis liquid products; Current trends in polymer science; Vol. 21 - Lyapkov A. A. Aleksey Alekseevich; Bondaletova A. V. Anna Vladimirovna; Bondaletov V. G. Vladimir Grigoryevich; Melnik E. I. Elena Ivanovna; Soroka L. S. Ludmila Stanislavovna; Troyan A. A. Anna Alekseevna; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich) (2021, 2021)
Title screen